New Construction of a Chaotic Generator on the Lorenz Attractor - Abdallah M; Mohamed Sadek Ali-Pacha; Naima Hadj-Said; Adda Ali-Pacha (مجلة جامعة الانبار للعلوم الصرفة, 2012)
it be known that the chaotic phenomena can be obtained from relatively simple systems that are governed by a small number of variables. The system will then be deterministic, although its behaviour is unforeseeable. The chaotic generator hereby suggested is implemented under the 7.0 version of MATLAB software. It makes use exclusively, of the fundamental properties of chaotic systems; that are sensitivity to initial conditions and equations of strange attractor. All is done in order to set up systems with protected transmissions. As a matter of fact and in the long term, the unforeseeable behaviour of such systems is very much related to the extreme sensitivity of initials conditions. Another fundamental property is that the chaotic system is characterized by a strange attractor, within the space of state.